THE INFLUENCE OF QUALITY MANAGEMENT ON HIGHWAY CONSTRUCTION PROJECT PERFORMANCE - Oni Cahyono; Yohanes Pracoyo Widi P; Heri Sujatmiko (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The highway construction industry is experiencing serious problems in terms of achieving quality, cost, and project implementation time. These problems arise due to the weakness of the quality management system that has not been fully integrated into the project cycle. Projects that fail to meet quality standards result in waste of resources and reduce public trust in project implementers. This study aims to analyze the effect of quality management on the performance of highway construction projects systematically and in depth. This study uses a qualitative approach based on literature review to identify elements of quality management that play an important role in improving project performance. The results of the study indicate that quality standards, workforce training, effective communication, use of technology, and organizational culture have significant contributions to the quality of construction results. The study also found that external supervision, type of contract, and project leadership strengthen the sustainable quality system. The periodic evaluation system and stakeholder involvement strengthen the accountability of the quality of highway projects as a whole. The study concludes that structured and integrated quality management can improve project efficiency in terms of cost, quality, and time simultaneously. The study recommends strengthening the sustainable training system, implementing digital technology, and establishing a quality culture in the project organizational structure. Project organizations are advised to integrate the quality system into all lines of decision-making and technical implementation. Stakeholders must be involved from the planning stage to create a sense of ownership of the development results. This study is expected to be a reference in the development of a national quality system in the highway construction sector.